Raziskava napovednikov pametnega upravljanja mest - Hoxha, Visar (Urbani izziv, 2023)
This research pinpoints key drivers of smart governance in Prishtina, Kosovo, using a quantitative approach. A self-report survey with 1,536 respondents, selected through stratified probability sampling, provided the necessary data. Principal component analysis was applied to assess the questionnaire’s internal structure, and regression analysis helped reveal smart governance predictors. Two pivotal findings emerged concerning Prishtina’s smart governance. Smart city management and smart collaboration were the most significant determinants, with the former demonstrating a slightly stronger correlation. These results underscore the role of effective city management practices and stakeholder collaboration in directing governance outcomes in smart cities. In light of this, policymakers are advised to emphasize stakeholder collaboration in smart city initiatives. For Prishtina, this translates into increased cooperation, transparency, accessibility to data in management practices, and a focus on infrastructure and public services to enhance smart city governance.
Keywords: Kosovo; pametni urbani menedžment; pametno sodelovanje; pametno upravljanje; Priština; smart city management; smart collaboration; smart governance